Model Holistik dan Kontinu: Implementasi Praktis Pendidikan Agama Kristen (PAK) Berdasarkan Ulangan 6:6-7 dalam Kehidupan Keluarga Sehari-hari - Dalle, Semuel (JURNAL LUXNOS, 2025)
This study aims to analyze and develop an operational model for the implementation of Christian Religious Education (CRE) based on the Biblical mandate in Deuteronomy 6:6-7 for the nurturing of children within Christian families. The Christian family plays a vital and primary role in the faith education of children, a concept deeply rooted in the Deuteronomy 6:6-7 text. This verse emphasizes the parents' obligation to instill God's word repeatedly and consistently (continuously) and holistically, integrating it into all aspects of daily life—namely "when you sit in your house," "when you walk by the way," "when you lie down," and "when you rise up". However, field reality often shows a significant gap between this ideal condition and contemporary practice, where parents tend to delegate CRE responsibility to the church or school, leading to fragile faith in children. Therefore, this research not only reiterates the importance of the biblical command but specifically seeks to offer an applicable, measurable, and contextual implementation framework to help Christian families adapt to modern challenges such as technological disruption. The method employed is qualitative library research focusing on the design and analysis of a continuous and holistic non-formal implementation model. The results are expected to contribute a practical model for Christian parents, facilitating a shift from normative understanding to transformative faith nurturing practice.